Influence of Hypertension on the Incidence of Cardiovascular Disease in Two Rural Communities in Japan : The Tanno-Soubetsu Study - Obara, Fumio; Saitoh, Shigeyuki; Takagi, Satoru; Shimamoto, Kazuaki (Hypertension research, 2007)
The purpose of this study was to determine the relationship between hypertension and onset of cardiovascular disease in Japan. As part of an ongoing epidemiological survey of cardiovascular diseases in Hokkaido, Japan, 1,798 subjects (806 males and 992 females; mean age in the initial year of the survey, 58.6±11.8 years) were selected, after excluding subjects who had been taking antihypertensive drugs, from a total of 2,136 subjects who had undergone medical examinations in 1991 in the town of Tanno and in 1992 in the town of Sobetsu, two rural communities in Hokkaido. Height, weight, casual systolic and diastolic blood pressures in the sitting position and blood biochemical values of all subjects were measured, and the subjects were divided into blood pressure level groups according to the 1999 World Health Organization/International Society of Hypertension (WHO/ISH) criteria. The follow-up survey was concluded at the end of August in 1999. The endpoints in this study were onset of circulatory disease or death due to circulatory disease. During the follow-up period, circulatory diseases (ischemic heart disease or stroke) occurred in 94 of the subjects. The incidence rates of cardiovascular disease (per 1,000 persons/year) for subjects divided into blood pressure groups according to the 1999 WHO/ISH blood pressure classification were 6.24 for the optimal+normal blood pressure level group, 11.26 for the normal high blood pressure level group, and 15.83 for the grade 1–3 hypertension group. Thus, the incidence rate of circulatory disease increased as the blood pressure level increased, and there was a significant difference between the incidence rate in subjects in the grade 1–3 hypertension group and the incidence rate in subjects in the optimal+normal blood pressure level group ( p <0.05). In a Cox's proportional hazards model with onset of circulatory disease as the endpoint, diastolic blood pressure was shown to be an independent risk factor with a relative risk of 1.01. The results suggest that hypertension is an independent risk factor for onset of circulatory disease.